Examining a comparative depiction of crime in Smith and Nesbo's selected novels : an afro-western perspective - Malatji, Permission Agosi (University of Limpopo, 2019)
This study explores a literary comparative examination of crime between Africa and Scandinavia, with special attention to Botswana and Norway. Smith’s and Nesbo’s selected novels are used as primary texts for analysis. The novels are, therefore, set in two different areas. These writers depict crime from the African and European perspectives. Chapter One deals with a brief introduction, and the aim and objectives of the study. It also expands on the theoretical background and provides definitions of terms that are used in this paper. Chapter Two presents views from various scholars on crime. This study is based on an Afro-Western approach of literary analysis. In other words, there are thoughts by both African and Western writers which assist in determining possible and noticeable similarities and differences, on the issue of crime. Chapter Three analyses crime from an African perspective while Chapter Four discusses crime from a Western point of view. Each of these chapters reflects on crime through character portrayal and depiction within its context. Chapter Five is a comparative analysis of both novels. The chapter identifies possible similarities and differences, mainly of the depiction of crime in different settings – Africa and Scandinavia, committed by blacks and whites. However, the structural and linguistic approaches of both the novels are also reviewed, assisting in discovering the life, in comparison, of the authors. The last chapter (Chapter Six), is a conclusion of the study and future suggestions. Basically, the study argues that blacks only should not be portrayed as perpetrators, but that whites too can be culprits. Again, there should be an equal of measurement on the weight and honour of the two races. Lastly, the moral is that without considering skin colour, financial and social backgrounds, justice must be served equally. Hence, whoever is caught in any form of wrongdoing, they must be given the appropriate punishment – regardless of race, colour, religious creed, gender, financial and social background. Key Words: Crime, Afro-Western, Marxism, suspense, detective, identity, puzzle, fix, accumulation, class, characterisation and setting
Thesis (M. A.(English Studies)) --University of Limpopo, 2019
Keywords: Crime; Afro-Western; Marxism; Suspense; Detective; Identity; Puzzle; Fix; Accumulation; Class; Characterisation and setting; Biographical fiction; Semiotics